SUR L’ADAPTATION AU NIVEAU (A1, A2, B1) DE LA LANGUE ROUMAINE COMME LANGUE ÉTRANGÈRE DANS LA MÊME SPHÈRE LEXICALE - ROMAN, Diana-Maria (Studia Universitatis Babeș-Bolyai Philologia, 2017)
The adaptation to the level (A1, A2, B1) of the Romanian language as a foreign language within the same lexical sphere. Along with the finalization of the courses part of the project „Continuing education for teachers from the post-secundary education who teach Romanian to the national minorities, POSDRU agreement 87/1.3/S/63909”, the work tool of the Language, Culture and Romanian Civilization Department, A Minimalist Description of the Romanian Language (A1, A2, B1, B2), has finished, and the profile levels of the linguistic competence has came along much more clearly. Thus, based on this document which has already become legitimate within the department, drafted from a communicative-functional perspective, with a very well shaped structure in some large sections, within each level: communicative functions, elements of communication construction, lexical elements, expression of circumstances, sentence construction, etc., it has been produced, within the aforementioned project, a series of audio-visual materials on levels, with specific worksheets. These visual aid materials, necessary for the development of the oral and written communication skills, have been drafted according to a different lexical sphere, for example, animals, health, travel, weather, school, personal presentation, etc., in such a manner that all of the three levels have been covered. The purpose of the present paper is to exemplify, based on the suggested texts, how the adaptation has been made concretly, more precisely, how the passage from A1 to A2 and B1 has been made, within the same lexical sphere, according to all of the variables enforced by the linguistic tool aforementioned. Rezumat. Adaptarea la nivel (A1, A2, B1) a limbii române ca limbă străină în cadrul aceleiaşi sfere lexicale. Odată cu finalizarea cursurilor din cadrul proiectului „Perfecţionarea cadrelor didactice din învăţământul preuniversitar care predau limba română minorităţilor naţionale, contract POSDRU 87/1.3/S/63909”, instrumentul de lucru al Departamentului de Limbă, Cultură şi Civilizaţie Românească, Descrierea minimală a limbii române (A1, A2, B1, B2), s-a finisat, iar profilul nivelurilor de competenţă lingvistică s-a conturat mult mai clar. Astfel, pe baza acestui document devenit deja legitim în domeniu, redactat din perspectivă comunicativ-funcţională, cu o structură foarte bine delimitată în câteva secţiuni mari, în interiorul fiecărui nivel: funcţii comunicative, elemente de construcţie a comunicării, elemente lexicale, exprimarea circumstanţelor, construcţia enunţului, mijloace de realizare a coeziunii şi coerenţei în textul vorbit/scris, etc., s-au produs, în cadrul proiectului amintit anterior, o serie de materiale audio-video pe nivel, cu fişe de lucru specifice. Aceste materiale didactice, necesare dezvoltării competenţelor de comunicare orală şi scrisă, au fost redactate conform unei sfere lexicale diferite, de exemplu, animale, timp liber, sănătate, călătorii, vremea, şcoala, prezentare personală etc., astfel că toate cele trei niveluri au fost acoperite. Scopul lucrării de faţă este de a exemplifica, pe baza textelor propuse, cum s-a făcut, concret, adaptarea la nivel, mai exact cum s-a realizat trecerea de la A1 la A2 şi la B1, în cadrul aceleiaşi sfere lexicale, ţinând cont de toate variabilele impuse de instrumentul lingvistic sus-amintit. Cuvinte-cheie: nivel de competenţă lingvistică, instrument lingvistic, adaptare la nivel, sferă lexicală, materiale didactice